1988
DOI: 10.1203/00006450-198804000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Digitalis Receptor in Erythrocytes from Preterm Infants and Adults

Abstract: ABSTRACT. We compared adrubidium by erythrocytesThe membrane Na", K' , ATPase is considered by most auof preterm infants and adults as a measurement of their thorities to be the pharmacologic receptor for digitalis glycosides Na+, K+, ATPase enzyme system. In neonates, total uptake (7). By specifically inhibiting this enzyme, higher intracellular (0.92 2 0.13 pg/106 cells) and specific uptake (0.64 f concentrations of sodium are achieved; exchange of increased 0.076 pg/106 cells) were significantly higher than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 7 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…The need for higher doses could be due to a larger concentration of N π -K π -ATPase in the myocardium (Kjeldsen & Grøn 1990). Other studies have suggested a higher erythrocyte binding capacity of digoxin (Koren et al 1988), which could provide a pharmacodynamic explanation of the increased demand of digoxin to achieve a given effect in infants compared to adults. Higher concentrations would thus be necessary for sufficient clinical effect, but the vagal effects and the risk of a critical increment in P-Potassium are still present and should be dealt with.…”
Section: Discussionmentioning
confidence: 99%
“…The need for higher doses could be due to a larger concentration of N π -K π -ATPase in the myocardium (Kjeldsen & Grøn 1990). Other studies have suggested a higher erythrocyte binding capacity of digoxin (Koren et al 1988), which could provide a pharmacodynamic explanation of the increased demand of digoxin to achieve a given effect in infants compared to adults. Higher concentrations would thus be necessary for sufficient clinical effect, but the vagal effects and the risk of a critical increment in P-Potassium are still present and should be dealt with.…”
Section: Discussionmentioning
confidence: 99%